TOLERANCE EDUCATION VALUES IN BAJRANGI BHAIJAAN FILM - Hidayat, Rahmat; Nasution, Yusri Purnama Anju (Universitas Dharmawangsa, 2020)
In a life filled with diversity like this, a spirit of tolerance must be instilled early on. Resources that can be used can be in the form of electronic media such as films. And the film by the author is Bajrangi Bhaijaan. In this film a lot is told about life that is very tolerant, not only that this film also tells about how a human person appreciates a difference in family life, and socially. On the problems studied, what are the values of tolerance education contained in the film Bajrangi Bhaijaan? And the purpose of this study was to determine the values of tolerance education contained in the Bajrangi Bhaijaan film. This research is a qualitative study, the type of research conducted is library research. The data collection method used is the documentation method with the data source used in the study, namely primary data and secondary data. By taking the object of Bajrangi Bhaijaan film studies, the data collection technique uses content analysis techniques. The results of this study indicate that Bajrangi Bhaijaan film is a film that can be used as an alternative in learning, especially religious tolerance education. Because in this film contains the values of religious tolerance education, there are two kinds of religious tolerance, namely: 1) Tolerance between religions in the form of mutual assistance, mutual respect which includes respecting differences in beliefs, respecting other religious shrines, and valuing differences of opinion, mutual understanding, respecting the rights of everyone and establishing good relations with people of other faiths. 2) religious internal tolerance in the form of good prejudice and fair conduct to all parties